(untitled) (Forum Penelitian Agro Ekonomi, 2016)
English During the last two decades, through INPRES No.9/1975, Indonesian government implemented policies that promote the domestic sugar industry. However, through INPRES No.5/1998, the former policy was declared ended or terminated. This study is intended to explore and discuss the sugar mill industry between those two periods of INPRES. The study showed that during the last five years of INPRES No.9/1975, there was a significant decrease in the overall performance of the East Java sugar industry ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬ÃƒÂ¢Ã¢â€šÂ¬Ã‚Â on the areas of (1) production areas, yield or productivity, (2) rendemen, (3) sugarcane farmers’ income. There are several steps need to be taken to increase the overall performance of the East Java sugar industry: (1) letting the sugar factory be responsible to handle its farmers’ fertilizers needs (include supply and distribution), (2) introducing the new high yield varieties, better on-farm practice (such as local/specific fertilizer’s package or recommendation), proper ratoon technology, (3) implementing better working plan (between cutting and post-harvest or transporting time). ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â Indonesian Selama dua dekade lebih pemerintah melakukan trobosan kebijakan di bidang industri gula melalui INPRES No.9/ 1975, sejak tahun 1998 melalui INPRES No.5/ 1998 kebijakan tersebut dihentikan. Tulisan ini bertujuan membahas kinerja industri gula di Jawa Timur menjelang berakhirnya INPRES No.9/ 1975. Hasil evaluasi, menunjukan bahwa pada lima tahun terakhir menjelang dicabutnya INPRES No.9/ 1975 kinerja industri gula di Jawa Timur mengalami penurunan yang cukup signifikan, baik terhadap perkembangan luas tanam, produktivitas, rendemen maupun terhadap pendapatan riil petani tebu. Beberapa hal yang perlu di lakukan untuk meningkatkan kinerja industri gula tersebut antara lain: (1) Menyerahkan penggandaan dan distribusi pupuk kepada pihak PG agar tersedianya pupuk di tingkat petani lebih terjamin; (2) PeningkatanÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â efisiensi melalui perbaikan teknologi budidaya, varitas unggul, rekomendasi pemupukan spesifik lokasi dan teknologi keprasanÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â (ratoon) yang tepat guna; (3) Perencanaan luas dan waktu tanam yang tepat sehingga waktu tebang angkut bisa optimal.